Analisis Percepatan Gravitasi Lokal melalui Pendekatan Eksperimental dan Simulatif pada Bandul Fisis - Utami, Ika Wahyu; Sulistiyono, Taufiq Yudi; Suudi, Bambang Cholis; Najih, Muhammad; Putri, Larasati Rizky; Mayusda, Idriwal; Rafael, Garren Benaya (Universitas Pendidikan Ganesha, 2025)
Accuracy in measuring local gravitational acceleration remains a challenge due to the limitations of conventional experimental approaches and the influence of dynamic system conditions. Furthermore, few studies have integrated numerical simulation methods to enhance precision in the context of nonlinear oscillatory motion. This study aims to conduct an in-depth analysis of the dynamics of a damped physical pendulum and to evaluate the accuracy of local gravitational acceleration measurements by integrating experimental methods with numerical simulations. This is a quantitative study employing a quasi-experimental design. The research subject consisted of a single set of physical pendulum apparatus in the form of a homogeneous metal rod, with no human participants involved. Data were collected by measuring the oscillation period using a high-accuracy digital stopwatch and the effective length using a roll meter. Instruments were validated based on classical physics principles and result consistency tests. Numerical simulations were performed using the fourth-order Runge-Kutta method (ODE45). Data analysis included quantitative descriptive analysis, comparative analysis, relative error evaluation, and uncertainty identification. The results showed that the experimental gravitational acceleration value closely approximated the theoretical value, with a low relative error. It is concluded that integrating experimental and simulation approaches provides a more comprehensive understanding of pendulum dynamics and improves the accuracy of local gravity measurements. The findings imply the need for more complex dynamic models to support precision measurements in various fields such as geophysics, engineering, and education.